Politik Kontemporer: Tantangan Dan Prospek Dalam Membangun Demokrasi Yang Berkelanjutan - R. Stevanus Bayu Mangkurat; Risalatu Mirajiah (Journal of Government and Politics (JGOP), 2021)
This research examines contemporary political phenomena and the challenges and prospects associated with sustainable democratic development. Contemporary politics is a topic that is relevant in various countries around the world, where there are significant political changes that affect social, economic and political development. This article examines challenges such as democratic crises, political conflicts, limited access to political and economic rights, and threats to environmental sustainability, as well as prospects such as active community participation, use of information and communication technology, and participation in general elections. This article also highlights the importance of citizen participation in the political process, strengthening the legal system and protecting human rights, and increasing information disclosure and access to the media. Through collaboration between political leaders and citizens, building a more inclusive political system and promoting citizen participation in the political process can be achieved, creating a better and more sustainable future for our society)